2008
DOI: 10.1074/jbc.m801646200
|View full text |Cite
|
Sign up to set email alerts
|

Signaling-mediated Functional Activation of Inducible Nitric-oxide Synthase and Its Role in Stimulating Platelet Activation

Abstract: Nitric oxide (NO) is a short lived secondary messenger, synthesized by nitric-oxide synthases (NOS). It is believed that the activity of inducible NOS (iNOS) is regulated primarily at the transcription level by inducing expression of iNOS mRNA and protein, which then continuously produces NO, until its degradation. Platelets do not have the nuclear transcriptional regulatory mechanisms of the iNOS gene and are believed to generate NO in response to agonist stimulation via endothelial NOS (eNOS). However, here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…This may suggest that the level of NO production in EPCs via iNOS is not sufficient to affect platelet function. Recently, Marjanovic et al 36 have shown that NO synthesis during platelet activation not only involves eNOS but is also mediated by the constitutively expressed platelet iNOS. iNOS-derived NO is important in promoting platelet activation, both ex vivo and in vivo, via a cGMP-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that the level of NO production in EPCs via iNOS is not sufficient to affect platelet function. Recently, Marjanovic et al 36 have shown that NO synthesis during platelet activation not only involves eNOS but is also mediated by the constitutively expressed platelet iNOS. iNOS-derived NO is important in promoting platelet activation, both ex vivo and in vivo, via a cGMP-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Both eNOS and iNOS are expressed and functional in platelets. [2][3][4][5][6] The major effect of NO is mediated by its cytosolic receptor, soluble guanylyl cyclase (sGC). The roles of the NO/sGC/cGMP pathway in platelet activation have been investigated for Ͼ 3 decades.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding time was measured as described. 10 Submitted March 31, 2010; accepted June 2, 2010. Prepublished online as Blood First Edition paper, June 16, 2010; DOI 10.1182 DOI 10.…”
mentioning
confidence: 99%